Peningkatan Hasil Belajar Siswa dengan Proyek Pembuatan Mading Tentang Keberagaman - Suyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This research is entitled "Improving Student Learning Outcomes with the Wall-Making Project on Diversity". The subjects of this research were all students in class VIII A at SMP PGRI 4 Matesih for the 2022/2023 academic year. The aims of this research are: (1) To find out the learning outcomes of class VIII A students at SMP PGRI 4 Matesih before learning was carried out with the Mading Making Project, (2) To find out how the Mading Making Project can improve the learning outcomes of class VIII A students at SMP PGRI 4 Matesih, and (3) To find out the results of improving the learning outcomes of class VIII A students at SMP PGRI 4 Matesih after learning by making a wall-mounted wall-making project on the subject of Diversity. Based on the aspects to be achieved, the Classroom Action Research (CAR) method was used in this research because in general PTK is very suitable for improving the quality of research subjects. Based on the research results, it was found that the Mading making project could improve student learning outcomes on the subject of Diversity.